nit-2, the major positive-acting nitrogen regulatory gene of Neurospora crassa, encodes a sequence-specific DNA-binding protein. - Fu, Y H (1990)
The nit-2 major nitrogen regulatory gene of Neurospora crassa turns on the expression of various unlinked structural genes that specify nitrogen-catabolic enzymes under nitrogen-limitation conditions. The nit-2 gene encodes a protein of 1036 amino acid residues with a single zinc finger and a downstream basic region that may make up a DNA-binding domain. The zinc-finger domain of the NIT2 protein was synthesized in two ways to examine its DNA-binding activity with gel-band-mobility shift and DNA-footprint experiments. The NIT2 protein binds to specific DNA recognition elements that are located upstream of nitrogen-regulated structural genes. Each recognition element contains at least two copies of a core sequence whose consensus is TATCTA.